Pengaruh Self-Control terhadap Grit pada Mahasiswa yang Menjadi Panitia Kegiatan - Dwi Cahya Oktarina; Ira Adelina (Universitas Kristen Maranatha, 2020)
College students who take part in organizational committee activities have greater responsibilities than college students who do not take part in committee activities. Considering the difficulties in learning and organizational activities, they need to make a continuous effort and focus on the goal of completing studies. This research was conducted to determine the effect of self-control on grit in students who participated in the organizational committee. There are 175 research respondents who join in student senate committee. Data analysis techniques using simple linear regression method. The results of this study found that there is a significant influence (R2 = 48.4%, ? = 0.696, and ? = 0.000) of self-control of grit in students who join in the organizational committee. Keywords: Self-Control, Grit, Organizational Comittee Students